EXPLORING THE SEMIOTICS OF LANGUAGE: UNRAVELING MEANING IN ENGLISH DISCOURSE, CULTURAL AND SOCIAL IMPLICATIONS - Saifullah; Muhammad Asif; Zarmina Anwaar; Qurat-ul-Ain; Syeda Raheela Bibi; Muhammad Shah Zaib Hayat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
This study explores the semiotics of language in English dialogue, hoping to decipher the complex method by which meaning is constructed. The study delves into how the cultural and contextual comprehension of communication in English is facilitated by evaluating a wide range of linguistic indicators such as phonological markers, lexical choices, accents, idioms, proverbs, and metaphors. Interview and survey data can be analyzed qualitatively to reveal recurrent themes and patterns that tell us more about the social and cultural meanings of words and phrases. The results have implications for linguistics and semiotics, highlighting the power of semiotics in determining how we understand what we hear in English.